Antibody-drug conjugates and predictive biomarkers in advanced urothelial carcinoma - Fenton, Sarah E.; VanderWeele, David J. (Frontiers in Oncology, 2023)
The use of antibody-drug conjugates (ADCs) is expanding in several malignancies, including urothelial carcinoma where two of these medications have been approved for use and several others remain under study. ADCs act by binding to specific cell surface proteins, delivering anticancer agents directly to the target cells. Preclinical studies suggest that loss of these surface proteins alters sensitivity to therapy and expression of target proteins vary significantly based on the tumor subtype, prior therapies and other characteristics. However, use of biomarkers to predict treatment response have not been regularly included in clinical trials and clinician practice. In this review we summarize what is known about potential predictive biomarkers for ADCs in UC and discuss potential areas where use of biomarkers may improve patient care.